Capturing users' experience of UK out-of-hours primary medical care: piloting and psychometric properties of the Out-of-hours Patient Questionnaire. Issue 6 (30th November 2007) - Campbell, J L; Dickens, A; Richards, S H; Pound, P; Greco, M; Bower, P
Abstract : Background and objective: Provision of out-of-hours care in the UK National Health Service (NHS) has changed in recent years with new models of provision and the introduction of national quality requirements. Existing survey instruments tend to focus on users' satisfaction with service provision; most were developed without undertaking supporting qualitative fieldwork. In this study, a survey instrument was developed taking account of these changes in service provision and undertaking supporting qualitative fieldwork. This paper reports on the development and psychometric properties of the new survey instrument, the Out-of-hours Patient Questionnaire (OPQ), which aims to capture information on the entirety of users' experiences of out-of-hours care, from the decision to make contact through to completion of their care management. Methods: An iterative approach was undertaken to develop the new instrument which was then tested in users of out-of-hours services in three geographically distributed UK settings. For the purposes of this study, "service users" were defined as "individuals about whom contact was made with an out-of-hours primary care medical service", whether that contact was made by the user themselves, or via a third party. Analysis was undertaken of the acceptability, reliability and validity of the survey instrument. Results: The OPQ tested is a 56-item questionnaire, which was distributed to 1250 service users. Respondents were similar in respect of gender, but were older and more affluent (using a proxy measure) than non-respondents. Item completion rates were acceptable. Respondents sometimes completed sections of the questionnaire which did not equate to their principal mode of management as recorded in the record of the contact. Preliminary evidence suggests the OPQ is a valid and reliable instrument which contains within it two discrete scales—a consultation satisfaction scale (nine items) and an "entry-access" scale (four items). Further work is required to determine the generalisability of findings obtained following use of the OPQ, especially to non-white user populations. Conclusion: The OPQ is an acceptable instrument for capturing information on users' experiences of out-of-hours care. Preliminary evidence suggests it is both valid and reliable in use. Further work will report on its utility in informing out-of-hours service planning and configuration and standard-setting in relation to UK national quality requirements.